Pluripotency of embryonic stem cells lacking clathrin-mediated endocytosis cannot be rescued by restoring cellular stiffness - Mote, Ridim D. (J Biol Chem, 2021)
Mouse embryonic stem cells (mESCs) display unique mechanical properties, including low cellular stiffness in contrast to differentiated cells, which are stiffer. We have previously shown that mESCs lacking the clathrin heavy chain (Cltc), an essential component for clathrin-mediated endocytosis (CME), display a loss of pluripotency and an enhanced expression of differentiation markers. However, it is not known whether physical properties such as cellular stiffness also change upon loss of Cltc, similar to what is seen in differentiated cells, and if so, how these altered properties specifically impact pluripotency. Using atomic force microscopy (AFM), we demonstrate that mESCs lacking Cltc display higher Young's modulus, indicative of greater cellular stiffness, compared with WT mESCs. The increase in stiffness was accompanied by the presence of actin stress fibers and accumulation of the inactive, phosphorylated, actin-binding protein cofilin. Treatment of Cltc knockdown mESCs with actin polymerization inhibitors resulted in a decrease in the Young's modulus to values similar to those obtained with WT mESCs. However, a rescue in the expression profile of pluripotency factors was not obtained. Additionally, whereas WT mouse embryonic fibroblasts could be reprogrammed to a state of pluripotency, this was inhibited in the absence of Cltc. This indicates that the presence of active CME is essential for the pluripotency of embryonic stem cells. Additionally, whereas physical properties may serve as a simple readout of the cellular state, they may not always faithfully recapitulate the underlying molecular fate.